2020
DOI: 10.3389/fcvm.2020.590688
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injury at Early Stage and Its Association With the Risk of Death in COVID-19 Patients: A Hospital-Based Retrospective Cohort Study

Abstract: Background: There are growing evidence demonstrating that coronavirus disease 2019 (COVID-19) is companied by acute myocardial injury. However, the associations of SARS-CoV-2-induced myocardial injury with the risk of death and prognosis after discharge in COVID-19 patients are unclear.Methods: This prospective cohort study analyzed 355 COVID-19 patients from two hospitals in different regions. Clinical and demographic information were collected and prognosis was followed up.Results: Of 355 hospitalized patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Several studies conducted by our group have highlighted a series of marked changes in routine blood indices and associated instances of multiple organ injury in patients with coronavirus disease 2019 (COVID-19) [24][25][26][27], spurring the present analysis of IL-27 levels and related clinical findings in CAP patients. Overall, these analyses revealed a negative correlation between serum IL-27 and lymphocyte levels in CAP patients, whereas IL-27 concentrations were positively correlated with the counts of WBC, neutrophils and monocytes, as well as key indicators of myocardial, renal, and hepatic function.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies conducted by our group have highlighted a series of marked changes in routine blood indices and associated instances of multiple organ injury in patients with coronavirus disease 2019 (COVID-19) [24][25][26][27], spurring the present analysis of IL-27 levels and related clinical findings in CAP patients. Overall, these analyses revealed a negative correlation between serum IL-27 and lymphocyte levels in CAP patients, whereas IL-27 concentrations were positively correlated with the counts of WBC, neutrophils and monocytes, as well as key indicators of myocardial, renal, and hepatic function.…”
Section: Discussionmentioning
confidence: 97%
“…A series of studies from our team found that the obvious change of blood routine indices and multiple organ injury were complicated with the disease of pneumonia [21][22][23][24]. Consequently, the associations of serum IL-27 and clinical features were analyzed among CAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we evaluated the association between serum S100A12 and inflammatory cytokines and found a positive correlation. Several previous studies from our team had revealed that lymphocyte reduction, liver dysfunction, renal dysfunction, and myocardial injury were observed in patients with Coronavirus disease 2019 (32)(33)(34)(35). Publishing data have revealed that Streptococcus pneumoniae or other pathogen infection rapidly initiated an inflammatory response.…”
Section: Discussionmentioning
confidence: 96%